Morphological and molecular evidence reveals a new species of Sipyloidea (Phasmatodea: Lonchodidae: Necrosciinae: Necrosciini) from Yunnan Province, China - Wang, Zi-Zhao; Zhu, Zi-Hao; Wang, Xing-Min (Zootaxa, 2026)
This paper describes a new species of the genus Sipyloidea Brunner von Wattenwyl, 1893 from Yunnan Province, China based on morphological and molecular evidence: Sipyloidea brachyptera sp. nov.. A taxonomic identification key for females of this genus in China is also provided.